Designing a Theory of Change: Remote Training with Ethiopian Universities - Grossi, Amanda; Dinku, Tufa; Belay, Berhanu (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A remote two-day training with Ethiopian universities on the topic of Designing a Theory of Change was convened from February 27 to February 28, 2023, by the International Research Institute for Climate and Society (IRI) of the Columbia Climate School, in close collaboration with the International Livestock Research Institute (ILRI). The workshop, which was organized as part of the World Bank’s Accelerating the Impacts of CGIAR Climate Research for Africa (AICCRA) project, brought together 9 participants from 6 universities across Ethiopia to train them on the basics of theories of change and how to lead students through the process of their design. This interactive and practical remote workshop on designing theories of change was a demand-driven training to help Ethiopian universities piloting the Climate Risk Management in Agriculture (CRMA) curriculum better implement Chapter 5 of the curriculum where such evaluation concepts are integrated.